Education about stoma on self-care ability in colorectal cancer patients with colostomy - Naziyah Naziyah; Cholisah Suralaga; Rizki Hidayat (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Colon canceris cancer in the colon or rectum. The colostomy is a surgically made hole in the large intestine that allows feces to flow in a pouch on the abdominal wall. Colostomy actions can affect the patient's physical and psychological changes. This happens because physically there are changes in defecation patterns, diet, bag use, skin care around the stoma, odor, and so on. Most complications occur at home. Prevention is the main key, early detection can catch serious complications.Purpose: To determine the effect of health education on the stoma care capabilities in colon cancer patients with colostomy at MRCCC Siloam Hospitals Semanggi.Method: The research design was quasi-experimental with a one-group pre and post-test design. The sample in this study was 16 respondents selected using a purposive sampling technique. The research instrument used a knowledge questionnaire and skills observation. Data analysis used the Wilcoxon Signed Ranks Test.Results: The Wilcoxon Signed Ranks Test obtained a ρ-value of 0.000 (ρ<0.05) which means that H0 is rejected and Ha is accepted, which means that there is an effect of health education on the stoma care capabilities in colon cancer patients with colostomy at MRCCC Siloam Hospitals Semanggi.Conclusion: There is an effect of health education on the stoma care ability of colon cancer patients with a colostomy at MRCCC Siloam Hospitals Semanggi.